Effect of Dietary Palm Stearin Supplementation on Rumen Degradability and Fermentation Characteristics in Ruminants - rukkiya siddiqui; V.B. Chaturvedi; Anju kala; Pranav vyavahare (The Indian Journal of Animal Sciences, 2026)
The present study was conducted to evaluate the ruminal degradability of palm stearin and its effects on rumen fermentation in fistulated buffaloes. Three animals were allotted to a 3×3 Latin Square Design and fed diets containing 0% (T₀), 8% palm stearin (T₁), and 8% palm stearin with 1% sodium bicarbonate (T₂). Palm stearin degradability was assessed using the nylon bag technique, while rumen fermentation parameters were measured at the end of each feeding period. Results showed that palm stearin exhibited high rumen bypass characteristics, with more than 75% of the fat remaining undegraded even after 48 hours of incubation. Supplementation of palm stearin did not significantly affect rumen pH, ammonia nitrogen, lactic acid, or volatile fatty acid concentrations, indicating stable rumen fermentation across treatments. Inclusion of sodium bicarbonate had no adverse effect on fat degradability or fermentation patterns. Overall, the study demonstrated that palm stearin is a highly inert, saturated fat source that can be effectively used as a natural bypass fat to enhance dietary energy without disturbing rumen function in buffaloes.